Does International Humanitarian Law have an expiration date? : The temporal dimension of prolonged belligerent occupations: a case study of Palestine (Journal of the Spanish Institute for Strategic Studies, 2023)
The aim of this paper is to examine the suitability of International Humanitarian Law (IHL) as a legal framework for protracted belligerent occupations. Through a case study focusing on the occupation of Palestine, we will try to shed light on the extent to which the provisions of IHL are legally applicable to belligerent occupations that are significantly protracted in time and, if so, whether the temporal element requires adjustments in the application of this body of law. The results of our study suggest that, while the law of belligerent occupation may authorize differential legal treatment for nationals of the occupying state and those of the occupied territory, this does not mean that the occupant can establish a system of discrimination and religious oppression in the long term, under the legal cover that it is only temporary.
Keywords: belligerent occupation; ius in bello; Israel; Palestine